أثر التقارير الإدارية حول الضوابط الداخلية في التغلب على مشكلات التقارير المالية والمحاسبية (دراسة نوعية مقارنة في الشركات المساهمة العامة الأردنية) - جعارة, أسامه عمر (Université de M'sila, 2010)
The issue of internal control reporting has recently been of considerable interest to the accounting profession, and has generated significant controversy, between the auditors accountants and users of financial reports, some of them have suggested that such reporting can serve to enhance internal control, and help to overcome the problems of financial reports. The aim of this paper is to provide an empirical evidence relevant to the debate about internal control reporting, through the comparison between a population of companies have or had prior internal control reports and other population of companies have not. Results indicate that the companies with management reports about internal controls have less problems than which have not the same reports. also, the number of small companies which have not a management report about internal controls, much relatively more than bigger of that companies which have a problems in it's financial reports.